The Psychometrics of the Children's Depression Inventory When Used With Children Who Are Chronically Ill and Matched Community Comparison Peers. (August 2019) - Saoji, Nikita; Baran, Julie; Gerhardt, Cynthia A.; Vannatta, Kathryn; Rotter, David; Trauth, Jeanette M.; Noll, Robert B.
The Children's Depression Inventory (CDI) is used to screen for depression in children aged 7 years to 16 years. The purpose of this study is to examine the psychometrics of the CDI in a sample of children who are chronically ill ( N = 350) and in a sample of matched community comparison peers ( N = 357), and determine if the psychometrics of the scale are similar in both groups. Data were aggregated from previous reports examining social and emotional functioning of children with six chronic diseases and matched comparisons. The CDI was completed in the homes of all participants. No significant differences between groups on CDI scores, distributions, reliability, or validity were observed. Findings suggest that the psychometrics of the CDI are similar for children with chronic diseases compared with typically developing children. The CDI may be an effective screening tool for use with children who have chronic health conditions.